Global forest governance legal concepts and policy trends - Maguire, Rowena; Edward Elgar Publishing (Northampton, Mass. : E. Elgar Pub., 2013)
This book identifies the fundamental legal principles and the governance requirements of sustainable forest management. An analytical model for assessing forest regulation is created which identifies the doctrinal concepts that underpin forest regulation (justice, property, sovereignty and governance). It also highlights the dominant public international institutions involved in forest regulation (UNFF, UNFCCC and WB) which is followed by analysis of non-state international forest regulation (forest certification and ecosystem markets). The book concludes by making a number of practical recommendations for reform of global forest governance arrangements and suggested reforms for individual international forest institutions.
pt. 1. Overview -- pt. 2. The doctrinal concepts underpinning forest regulation -- pt. 3. International regulation by public forest institutions -- pt. 4. Regulation by non-state forest institutions -- pt. 5. Conclusions.
Includes bibliographical references and index.
Keywords: Forest management; Electronic books